Economics of Fertilizer Application to Wheat Crop: The Results of a Survey in Lyallpur District (Notes and Comments) (The Pakistan Development Review, 1970)
Reliable knowledge about the contribution of various factors responsible for increasing agricultural production is indispensable for planning. This holds particularly for the fertilizer use, which has been recognized as one of the quickest and, perhaps, the cheapest means for increasing agricultural produc¬tion. In Pakistan the emphasis on planned development is gaining momentum and for this purpose more data and fuller information on fertilizer response are becoming increasingly essential. The Agricultural Research Stations in the country have been conducting experiments with a view to determining the extent to which the cropped yield may increase due to the application of fertilizer. But such experiments, because of their somewhat controlled nature in respect of certain factors, obviously can¬not tell us with a desired measure of accuracy as to what is actually happening at millions of private farms throughout the country. And, as such, the planning in this regard is apt to be wrong.